Corrosion protection of fiber-reinforced polymer-wrapped reinforced concrete - Gadve, S.; Mukherjee, Abhijit; Malhotra, S. (American Concrete Institute, 2010)
Reinforced concrete (RC) flexure members such as bridges, slabs, and beams that have been damaged due to the corrosion of steel reinforcement are often rehabilitated with fiber-reinforced polymer (FRP) composites. This paper investigates passive as well as active protection of the steel reinforcing bar in RC flexure members that are treated with surface bonded FRP. Passive protection is investigated using glass FRP (GFRP) and carbon FRP (CFRP) sheets that have been adhesively bonded to the beam specimens. Active protection has been studied using electrically conductive carbon fiber wraparounds as an anode while the reinforcing bar is used as a cathode. Accelerated corrosion is inflicted in RC beams by immersing them in saltwater and passing anodic current through the reinforcement. For investigating active protection, the adhesive has been modified to impart electrical conductivity. Specimens were exposed to a highly corrosive environment for a specified time. Flexure strength, mass loss, and half-cell potential are reported as metrics of performance of the samples. The proposed technique has been very effective in retarding the corrosion of steel.